Community Empowerment with Business Model Canvas on Hijab Hampers (Case Study @hampershijabku) - Annisa Farah Tadayyana Wa Mutsaqqof; Infusvania Putri Prakasiwi; Dhanar Intan Surya Saputra (Peneliti Teknologi Teknik Indonesia, 2022)
The world of fashion for hijab is a promising business because more and more Muslim women are familiar with the hijab trend. Now more and more Muslim women are interested in wearing the hijab. There are many interesting tips and tricks on how to wear the hijab. This makes us see a great opportunity to open a hijab business. From these problems, the contribution of this community service is to get complete information about the canvas business model on hijab hampers. This community service uses qualitative analysis methods to find out how big the role of the Canvas Business Model is for startup businesses to design improvement businesses. The method used is descriptive qualitative. The result of this service is that the community, especially millennials, supports the existence of this almost hijab business because it is very helpful, especially for both formal and non-formal events.